Cinema pandemia reflections on the underrated Netflix series La Révolution vis-à-vis current Philippine & international realities - San Juan, David Michael (2024)
Access online through this link: https://www.plarideljournal.org/article/cinema-pandemia-reflections-on-the-underrated-netflix-series-la-revolution-vis-a-vis-current-philippine-international-realities
Keywords: Netflix, Inc